2020
DOI: 10.1098/rsos.200625
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis identified long non-coding RNAs involved in the adaption of yak to high-altitude environments

Abstract: The mechanisms underlying yak adaptation to high-altitude environments have been investigated using various methods, but no report has focused on long non-coding RNA (lncRNA). In the present study, lncRNAs were screened from the gluteus transcriptomes of yak and their transcriptional levels were compared with those in Sanjiang cattle, Holstein cattle and Tibetan cattle. The potential target genes of the differentially expressed lncRNAs between species/strains were predicted using cis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Studies have shown that high-altitude hypoxic environments have an important impact on energy metabolism in animals ( 15 , 20 , 21 ). Similarly, we found many differentially expressed genes and signaling pathways related to glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that high-altitude hypoxic environments have an important impact on energy metabolism in animals ( 15 , 20 , 21 ). Similarly, we found many differentially expressed genes and signaling pathways related to glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This not only increases the complexity of the cardiometabolic network, but it may also promote aerobic respiration in cardiomyocytes and their differentiation [36–38]. At high altitude and in a hypoxic environment, the yak needs a higher metabolism to maintain body temperature, which may explain why the metabolic rate of yak is higher than in cattle living in low altitude areas [17, 39].…”
Section: Discussionmentioning
confidence: 99%
“…The transcription of tropomyosin might be regulated by lncRNAs MSTRG.1770.1 and MSTRG.24686 and transcription of titin by lncRNA MSTRG.11409.1. Tropomyosin and titin levels were downregulated in yak compared with the three cattle strains, which might facilitate the muscle contraction, since tropomyosin and titin plays an opposite role during the process of muscle contraction [91]. Whole-transcriptome analysis of yak and cattle heart tissues predicted several miRNAs/lncRNAs that are significantly enriched in high-altitude adaptation targeting T cell receptor signaling, VEGF signaling, and cAMP signaling [92] In Tibetan chickens, several key candidate Competing endogenous RNAs (ceRNAs) (DE lncRNAs-DE miRNAs-DE genes), which may play high-priority roles in the hypoxic adaptation of Tibetan chickens by regulating angiogenesis and energy metabolism, were identified [93].…”
Section: Epigenetic Adaptation Of Animals To High Altitudementioning
confidence: 96%